HUBUNGAN PENDIDIKAN, PARITAS DAN DUKUNGAN KELUARGA DENGAN PELAKSANAAN CONTINUITY OF CARE DI TPMB KELURAHAN SEKAR JAYA - Titik Aryanti; Suprida Suprida; Eka Rahmawati; Desmansyah Desmansyah (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Maternal and child mortality is also affected by midwifery care services that are not carried out continuously or consistently. COC is midwifery services through a continuous service model for pregnant women, childbirth, postpartum and family planning. Previously, midwifery services were provided for mothers and babies separately. This type of research is an analytic observational study with a cross sectional design or approach. The sample in this study was that part of the postpartum mothers who gave birth at TPMB, Sekar Jaya sub-district, at the time of the study, totaled 38 respondents. The type of data uses primary data, the dependent variable is the implementation of continuity of care, the independent variables are education, parity and family support. The results of bivariate research on the relationship between education, parity and family support with Continuity Of Care based on the chi square statistical test of education p-value 0.014 <0.05, parity p-value 0.034 <0.05 and family support p-value 0.000 <0.05 it was concluded that there was a relationship between education, parity and family support simultaneously with the Implementation of Continuty Of Care at TPMB Sekar Jaya Village, Baturaja OKU City in 2023. As for suggestions to TPMB, it is expected that health workers/staff educate the importance of continuing midwifery care starting from pregnancy, childbirth, BLL , postpartum and postpartum family planning, so as to minimize intervention in these mothers.